IMPLIKASI ADVISORY OPINION MAHKAMAH INTERNASIONAL TENTANG KONSEKUENSI HUKUM PENDUDUKAN ISRAEL ATAS WILAYAH PALESTINA - Azmi Nasyath Nabila; Muh Risnain; Ayu Riska Amalia (Mataram Journal of International Law, 2025)
On July 19th 2024, the International Court of Justice issued an advisory opinion affirming that Israel's occupation of Palestinian territories is illegal under international law. The opinion states that Israel has violated the principle of prohibition of acquisition of territory by force and the right of the Palestinian people to self-determination. Although non-binding, the advisory opinion has high normative power and provides a legal and moral basis for states and international organizations to act. This research aims to analyze the legal consequences and obligations of UN member states arising from the opinion, as well as to evaluate its effectiveness in promoting the resolution of international disputes. The method used is normative legal research with an international treaty, case, conceptual, and historical approach. Legal materials were collected through literature review and analyzed qualitatively. The results of theresearch indicate that although this opinion is not legally binding, it remains an important instrument in clarifying the legal status of an action, strengthening the legitimacy of the Palestinian diplomatic struggle, and encouraging global collective action. However, its substantial implementation is still hindered by international political factors, such as the fragmentation of member states' positions. Therefore, collective efforts are needed to strengthen the influence of advisory opinions in the enforcement of international law.